THE RIPHEAN MAGMATISM PRECEDING THE OPENING OF URALIAN PALEOOCEAN: GEOCHEMISTRY, ISOTOPES, AGE, AND GEODYNAMIC IMPLICATIONS - V. V. Kholodnov; G. Yu. Shardakova; G. B. Fershtater; E. S. Shagalov (Геодинамика и тектонофизика)
The rocks from different stages of the geodynamic evolution have been preserved in the Urals. In its geologic history, the least studied is the transition period between continental rifting and the beginning of oceanic spreading. This article presents the geochemical data on the Sr-, Nd-isotopes, zircon U-Pb (SHRIMP) ages for the MesoNeoproterozoic igneous rocks and associated ores from the Bashkir meganticlinorium (BMA) on the Urals western slope. A Large Igneous Province (LIP) formed there as a result of mantle plume activity during the Middle Riphean (1380–1350 Ma). Later on (1200–1100 Ma), short-term rifting took place, as evidenced by the Nazyam graben, which was followed by the complete break-up of the continental crust. For magmatic rocks in the age range of 1750–1200 Ma, the evolition of chemical composition OIB-type → E-MORB →N-MORB is observed. The εNd(t) values for the igneous rocks and the associated BMA ores vary from negative (–6) to positive ones (+5), and thus give evidence of the lithosphere mantle depletion with time. These facts and the Sr-isotope ratios for the magmatic rocks from the subsequent evolution stages confirm that the oceanic basin to the east of the East European platform started to open at the end of the Middle Riphean. For the Vendian-Cambrian, some traces of orogenes (Timanian stage) are observed. The development of the Uralian Paleozoic ocean started in the Ordovican and continued up to the Late CarboniferousPermian.